2016
DOI: 10.3791/54746
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Foramen Ovale Electrode Recordings in Drug-resistant Temporal Lobe Epilepsy Patients

Abstract: Approximately 30% of epilepsy patients are refractory to antiepileptic drugs. In these cases, surgery is the only alternative to eliminate/control seizures. However, a significant minority of patients continues to exhibit post-operative seizures, even in those cases in which the suspected source of seizures has been correctly localized and resected. The protocol presented here combines a clinical procedure routinely employed during the pre-operative evaluation of temporal lobe epilepsy (TLE) patients with a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…(1) Non-invasive tests, consisting of MRI, SPECT, EEG, and neuropsychological and personality studies (Martín et al, 1992(Martín et al, , 1994Maestú et al, 2000) and (2) If temporal lobe epilepsy was confirmed, foramen ovale electrodes were bilaterally implanted under general anesthesia (Figures 1A-F) and subsequent Video-EEG was recorded (Figure 1G; Pastor et al, 2004Pastor et al, , 2006Pastor et al, , 2008aPastor and Sola, 2008;Herrera-Peco et al, 2010Sanz-García et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…(1) Non-invasive tests, consisting of MRI, SPECT, EEG, and neuropsychological and personality studies (Martín et al, 1992(Martín et al, , 1994Maestú et al, 2000) and (2) If temporal lobe epilepsy was confirmed, foramen ovale electrodes were bilaterally implanted under general anesthesia (Figures 1A-F) and subsequent Video-EEG was recorded (Figure 1G; Pastor et al, 2004Pastor et al, , 2006Pastor et al, , 2008aPastor and Sola, 2008;Herrera-Peco et al, 2010Sanz-García et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In this way, eight electrodes for each lateral side were employed, yielding a total of 16 EEG monopolar recordings for each patient. EEG recordings were continuously acquired for a period of 5.2 ± 2.3 d at a sampling frequency of 500 Hz (NeuroWorks, XLTEK ® , Oakville, ON, Canada), exported to ASCII at 200 Hz, band-pass filtered in the range 0.5-40 Hz [25]. Epochs containing artifacts such as saturated electrical activity, electrode displacements, among others, were discarded.…”
Section: Eegmentioning
confidence: 99%
“…In each patient, six-contact platinum FOEs with 1-cm center-to-center spacing (AD-Tech, Racine, WI, USA) were inserted bilaterally under general anesthesia [20][21][22]. Correct implantation was assured using fluoroscopic imaging in the operating room.…”
Section: Neurophysiological Datamentioning
confidence: 99%
“…Correct implantation was assured using fluoroscopic imaging in the operating room. The overall procedure of FOE surgical implantation as well as typical scalp + FOE recordings may be visualized in reference [22]. Table 1 includes clinical information, presurgical studies evaluations, and overall diagnosis.…”
Section: Neurophysiological Datamentioning
confidence: 99%
See 1 more Smart Citation